Effect of Precursors Concentration on The Optical and Photoelectrochemical Properties of Bi₂S₃/TiO₂ Nanotubes Arrays Photoanode Synthesized by the SILAR Technique - Eko Martin Sinaga; Muhammad Iqbal Syauqi; Jarnuzi Gunlazuardi (Jurnal Kimia Sains dan Aplikasi, 2024)
The use of robust solar energy-driven photocatalysis materials to address the global energy and environmental crisis has gained significant attention in recent years. However, the wide band gaps in many robust semiconductor photocatalysts hinder their absorption of visible light from the solar spectrum. To address this issue, the modification of the large band gap semiconductor with the lower band gap material using the Successive Ionic Layers Adsorption and Reaction (SILAR) technique has emerged as an economical, accessible, and reproducible method for depositing nanoscale materials onto semiconductor substrates. This research aims to know how the concentration variation of cation and anion precursors in the SILAR technique affects the optical and photoelectrochemical properties of the resulting composite materials. Bi₂S₃ serves as a modifier for TiO₂ nanotube arrays (NTAs). The result shows that the cation-anion concentration ratio of 1:1.5 mM with five SILAR cycles gives the best photoelectrochemical performance, with a stable current density of 0.12 mA/cm², compared to pristine TiO₂ NTAs the current density of Bi₂S₃/TiO₂ NTAs is 15-fold. In addition, at each variation, the concentration ratio of cation and anion precursors decreases bandgap energy with each increase in the SILAR cycle.